2021
DOI: 10.32725/kont.2021.024
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and modifiable risk factors of a stroke

Abstract: Introduction: Stroke is one of the leading causes of death and disability in European countries. Prevention and the associated health literacy are among the effective tools for reducing the incidence of this disease and serve to reduce its consequences. Goal: To examine the relationship between socioeconomic factors of health literacy and modifiable risk factors in connection with ischemic stroke. Methods: A quantitative survey strategy. The research was conducted using the technique of a standardized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…25 Although there is no clear study explaining the relationship between stroke and HL, reducing certain modifiable risk factors with the level of HL may establish a strong link between stroke and HL. 26 Additionally, high HL levels are important for successful stroke management. 27 In a study by Pien et al 28 low HL levels were found to be higher in patients with a history of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…25 Although there is no clear study explaining the relationship between stroke and HL, reducing certain modifiable risk factors with the level of HL may establish a strong link between stroke and HL. 26 Additionally, high HL levels are important for successful stroke management. 27 In a study by Pien et al 28 low HL levels were found to be higher in patients with a history of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Research has indicated neurobiological factors (rather than the psychological response to disability) as the main factors associated with depression after a stroke [ 43 ]. Health literacy is a modifiable risk factor for ischemic stroke [ 44 ]. Jeong and Cha reported that patients’ interest in health ( p < 0.001), health literacy ( p = 0.037), age ( p = 0.001), and caregiver gender ( p = 0.028) are significant factors influencing the health behavior of patients with stroke [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is a modifiable risk factor for ischemic stroke [44]. Jeong and Cha reported that patients' interest in health (p < 0.001), health literacy (p = 0.037), age (p = 0.001), and caregiver gender (p = 0.028) are significant factors influencing the health behavior of patients with stroke [45].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to the fact that low health literacy is associated with less understanding of prescribed medication instructions ( Mayo-Gamble and Mouton, 2018 ) and problems in using preventive services ( Stormacq et al, 2019 ). As health literacy is considered the most important modifiable risk factor of socioeconomic differences in health ( šedová et al, 2021 ), future work should investigate tailored interventions considering health literacy among older adult stroke survivors.…”
Section: Discussionmentioning
confidence: 99%